Lymphoblastoids cell lines – Derived iPSC line from a 26-year-old myotonic dystrophy type 1 patient carrying (CTG)200 expansion in the DMPK gene: CHUQi001-A - Laurie Martineau; Véronique Racine; Siham Ait Benichou; Jack Puymirat (Stem Cell Research, 2018)
Human immortalized Epstein-Barr virus (EBV) lymphoblastoids cells line (LCLs) from a 26-year- old male affected by an adult form of myotonic dystrophy type 1 (DM1) disease and carrying 200 CTG repeats mutation in the blood was used to generate induced pluripotent stem cells (iPSCs) using the Sendai virus expressing KLF4, OCT4, SOX2 and C-MYC. The resulting iPSCs were EBV free, expressed the pluripotency markers, could be differentiated into the three germ layers in vitro, had a normal karyotype, and retained the genetic DM1 mutation. This iPSC line could be useful for the investigation of DM1 mechanisms.